A class of singular $k_i$-Hessian systems - Feng, Meiqiang (Topological Methods in Nonlinear Analysis, 2023)
Our main objective of this article is to investigate a class of singular $k_i$-Hessian systems. Among others, we obtain new theorems on the existence and multiplicity of positive radial solutions. Several nonexistence theorems are also derived.